1999
DOI: 10.7863/jum.1999.18.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of small hyperechoic renal cell carcinoma from angiomyolipoma: computer-aided tissue echo quantification.

Abstract: idespread use of ultrasonography and abdominal CT has increased the detection of small renal neoplasms, often found incidentally in asymptomatic patients. 1,2 RCC and AML are the most frequently occurring malignant and benign renal parenchymal tumors, respectively. Frequently small RCC are hyperechoic 1-3 and may mimic AML. Efforts were made to differentiate the two conditions on the basis of ultrasonographic characteristics such as intratumoral cysts, hypoechoic rim, and posterior acoustic shadowing. [3][4][5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
(40 reference statements)
1
9
0
3
Order By: Relevance
“…Ultrasound tissue characterization based on either USfrequency-dependent attenuation [14] or relative grayscale values measurements (compared with renal cortex) [15] have been recently evaluated in the diagnosis of solid renal tumors. Both tissue echo quantification techniques yield promising diagnostic aid in differentiating hyperechoic RCCs from AMLs.…”
Section: Us Tissue Characterizationmentioning
confidence: 99%
“…Ultrasound tissue characterization based on either USfrequency-dependent attenuation [14] or relative grayscale values measurements (compared with renal cortex) [15] have been recently evaluated in the diagnosis of solid renal tumors. Both tissue echo quantification techniques yield promising diagnostic aid in differentiating hyperechoic RCCs from AMLs.…”
Section: Us Tissue Characterizationmentioning
confidence: 99%
“…Most solid RCCs revealed lower echogenicity than AMLs in conventional US (Sim et al 1999). In the present study, solid RCCs in subjective analysis showed intense contrast enhancement at the arterial phase, whereas typical AMLs revealed a dotlike appearance at the arterial phase.…”
Section: Discussionmentioning
confidence: 96%
“…Most RCCs are hypoechoic on US, but approximately 30% of small RCCs appear hyperechoic, similar to small angiomyolipomas (AMLs) (Forman et al 1993;Jinzaki et al 1998;Yamashita et al 1992), which typically appear very bright, homogeneous and sharply marginated (H el enon et al 2001;Jinzaki et al 1998). Incidence of atypical iso-hypoechoic and slightly hyperechoic AMLs account for 6% and 29%, respectively (Taniguchi et al 1997;Jinzaki et al 1998;Sim et al 1999). …”
Section: Introductionmentioning
confidence: 98%
“…), wurde die Echointensi- tät des Tumors in Relation zu der zugehörigen Nierenrinde gesetzt. Im Gegensatz zu Sim [28] haben wir auf den Vergleich mit dem Nierensinus verzichtet, da die Echointensität des Nierensinus eine stärker variable Größe ist. Die Standardabweichungen wurden in Varianzen umgerechnet und dienten als Maß der Inhomogenität (I).…”
Section: Patienten Und Methodikunclassified
“…Bei der Untersuchung mit höherfrequenten Sonden sowie bei der Arbeit mit Harmonic Imaging wurden tendenziell höhere Echoquotienten gemessen. Die Echointensität kleiner Angiomyolipome und Nierenzellkarzinome wurde in Relation zu der Nierenrinde und dem Nierensinus gemessen [28]. Die Methode wurde auch mit verschiedenen Geräten zur Analyse von Nierenrinde und Markpyramiden evaluiert [29].…”
unclassified